A Stochastic Model of Corporate Lifespan Based on Corporate Credit Ratings - Ondrej Machek (International Journal of Engineering Business Management, 2013)
Credit rating agencies and corporate lifecycles have been a subject of interest for practitioners and academics during the recent period of worldwide economic and debt crises. In this article, we examine what corporate lifespan the credit rating agencies predict. We employ the reliability theory commonly used in engineering and solve a Markov model based on the credit rating transition matrices issued by the Standard & Poor's rating agency. The results show that every company will eventually default in the long-term. However, the mean time to default differs according to the initial conditions of the model, which are represented by the initial credit rating. We considered a company as having initial speculative grades of B and CCC/C and calculated the mean time to default and the time after which the business can be considered safe, with a probability of only 50%. We also determined the probabilities of the individual rating grades. We suggest assessing corporate business cycles in probabilistic terms, taking into account all possible states and initial conditions.